DEVELOPING ENGKLEK GAME USING LEARNING STYLES APPROACH TO TEACH ENGLISH VOCABULARY FOR 4TH GRADE STUDENTS OF SD MUHAMMADIYAH KAUMAN YOGYAKARTA IN ACADEMIC YEAR 2015/2016 - Agustia Pristiana Maulida; Sucipto Sucipto (Universitas Ahmad Dahlan)
This study was intended to develop Engklek Game using learning style approach as a media to teach English vocabulary for 4th grade students of SD Muhammadiyah Kauman Yogyakarta in academic year 2015/2016.The subject of the research was 4th grade students of SD Muhammadiyah Kauman Yogyakarta in academic year 2015/2016. The data of students’ needs and learning style was collected by the researcher by giving questionnaire, doing interviews and doing observations. The result of the data then was used to become considerations in developing Engklek Game. Then, the prototype of the product was evaluated by experts. There were English teacher as the expert in ELT and lecture of Elementary Education Department as the expert in learning styles. In order to find the effectiveness of Engklek Game, the implementation was done by giving pre-test, treatment and post-test to students. The data was calculated by using SPSS 16.00. After the implementation, the researcher did evaluation by analyzing the students’ responses to the media.The result of the evaluation done by the experts of ELT and learning styles showed that Engklek Game is suitable to be used as media to teach English vocabulary for 4th grade students of SD Muhammadiyah Kauman Yogyakarta in academic year 2015/2016. In other side, after the result of pre test and post test had been calculated, it can be seen that there was a significant enhancement of students in learning English vocabulary after taught using Engklek Game. While based on students’ response, it can be concluded that Engklek Game is appropriate to be used.